1982
DOI: 10.3109/10408368209107031
|View full text |Cite
|
Sign up to set email alerts
|

Analyte Stability in Clinical Chemistry Quality Control Materials

Abstract: Maximum stability of analytes in chemistry control materials is desired. Stability testing is customarily performed by manufacturers, both prior to distribution of products and during the period following distribution when the products are in the field. Users and evaluators of such materials periodically have reported on experienced stability of various analytes in distributed manufactured products. A wide variety of both testing protocols and definitions of acceptable stability have characterized published re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The variety of statistical approaches used to assess stability also affects the stability results. It has been reported that about 5 % of the results are expected to show instability due the choice of the statistics [16]. Therefore, recommended alternate approaches to using statistics in order to provide useful information depending on the nature and frequency of the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The variety of statistical approaches used to assess stability also affects the stability results. It has been reported that about 5 % of the results are expected to show instability due the choice of the statistics [16]. Therefore, recommended alternate approaches to using statistics in order to provide useful information depending on the nature and frequency of the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…We also studied the analyte stability. The definition of stability was a measured change in the concentration of analytes by the given method (Lawson et al, 1982). In the present study, we examined the effect of the selected acidic modifier concentration in the mobile phase on the stability of target compounds.…”
Section: Optimization Of Lc-q-tof/ms Analysismentioning
confidence: 99%